Factors predicting caregiver burden of children with autism spectrum disorder: a cross-sectional study - Khamenkan, Kanokjun; Poogpan, Jidapa; Apakang, Sittipong; Outanit, Wanna; Thongmee, Atayapon (Jurnal Ners, 2026)
Introduction: Caregivers of children with Autism Spectrum Disorder (ASD) face considerable psychological and physical burdens owing to the demands of caregiving. Identifying key predictors of caregiver burden, such as caregiver stress, quality of life, and child behavioral characteristics, is crucial for developing effective support interventions. This study aimed to examine factors that predict caregiver burden among those caring for children with ASD. Methods: This cross-sectional study included 91 caregivers selected by simple random sampling from a list of children with ASD who attended the Child Development Clinic (CDC). The data were collected using an instrument that included the Zarit Burden Interview (ZBI), Suanprung Stress Test-20 (SPST-20), World Health Organization Quality of Life Brief-Thai (WHOQOL-BREF-THAI), and Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using Pearson's correlation and multiple logistic regression. Results: Caregiver stress demonstrated the strongest positive association with caregiver burden (β = 0.431, p < 0.001), indicating that higher stress levels significantly increased the burden. Child behavioral difficulties also significantly predicted a greater burden (β = 0.356, p < 0.001). In contrast, caregivers’ quality of life (β = -0.175, p < 0.01) and child strength (β = -0.192, p < 0.01). Conclusions: Caregiver stress is the primary predictor of burden among those caring for children with ASD. Child behavioral difficulties further increase burden, while caregiver quality of life and child strength act as protective factors. These findings support interventions that reduce caregiver stress, address child behavioral challenges, and enhance caregiver well-being, thereby alleviating caregiver burden.